Conversion Of Waste Cooking Oil Into Biofuels Using Trimetallic Catalyst - Rashid, Nur Alya (Universiti Sains Malaysia, 2022)
Cooking oil is essential for daily used especially in restaurants, food manufacturers, and households. The cooking oil is mostly made up from palm, vegetable, coconut, or natural oils. However, the used cooking oil is often disposed through the drainage from the kitchen sinks. Nearly 50,000 tonnes of waste cooking oil derived from vegetable oils or animal fats were released into the environment without appropriate treatment. This could lead to emission of unpleasant odour and disturb the nearby residents. Therefore, recycling waste cooking oil into biofuels not only will benefit the transportation section but also help in waste management. Catalytic cracking is used in this study is to produce biofuel from waste cooking oil. In this study, different type of catalysts (Zeolite Y, Cu/Zeolite Y, Ni/Zeolite Y, Cu-Ni/Zeolite Y, Cu-Ni-Fe/Zeolite Y and Cu-Ni-Zn/Zeolite Y), operating temperature (300°C, 350°C and 400°C) and residence time (60, 90 and 120 minutes) were studied to determine their effects on catalytic cracking of the waste cooking oil. The as liquid yield, coke and gas yield were investigated for all the reactions. The liquid product was also anaylyzed with ASTM distillation. Through this study, the best operating parameters are; using tri-metallic catalyst Cu-Ni-Zn/Zeolite, the temperature of 350 ˚C and 60 minutes as it produced the highest liquid yield (78.43%), the lowest gas yield (21.44 %) and coke yield (0.13 %), and the lowest residues percentage (28 %) with high amount of hydrocarbon. The hydrocarbon yield consists of gasoline (1%), kerosene (16%) and diesel (55%).